The Work-Based Learning Student Handbook - Helyer, Ruth; Wall, Tony, 1979-; Minton, Ann; Lund, Amy (2021)
This volume will help work-based students to successfully navigate academia. It is a hands-on guide for learners, helping them to get the most out of their university experience.
Previous edition: 2015.
Includes bibliographical references and index.
Keywords: Study skills; Experiential learning; Education, Cooperative; College students -- Employment; Education